The investigation of presence coxiella burnetii in sheep and goat milk by the PCR - Kiliç, Ayşe (Ataturk Universitesi, 2017)
Q fever is a zoonotic disease caused by Coxiella burnetii bacteria, which shedding into largely ruminant animals with products such as milk, vaginal mucus and stools. Cattle, sheep and goats are primary C. burnetii reservoir hosts. In this study, 120 milk samples were collected from different sheep and goat herds which aborting and non-aborting and A PCR was performed with Trans 1 and Trans 2 primers derived from tranposon repetitive gen region. The milk samples obtained from herds belonging aborted sheep in Elazig and neighboring provinces showed a total of 10% were detected positivity, whereas the 3.33% milk sample taken from aborted goat herds were observed C. burnetii as positive by the PCR. The milk samples taken from non-aborted sheep and goat herds weren't observed positivity by the PCR test. As a result, it is aimed to investigate C.burnetii infection in goat and sheep milk samples obtained from belonging aborted and non-aborted flocks by molecular methods.
Koyun ve Keçi Sütlerinde Coxiella burnetii Varli?inin PCR ile Araştirilmasi
Keywords: C.burnetii; Milk; PCR